An empirical test of implied volatility in Singaporean structured warrants - Samsudin, Najmi Ismail Murad; Mohamad, Azhar (2018)
Options traders regard implied volatility a vital variable to determine profitability in options trading and use it to estimate the underlying stock’s volatility in the future. While it cannot predict market direction, it has a reputation for forecasting—to a certain extent—potential for large swings by the underlying stock. Once implied volatility is calculated, traders can estimate how high and low the stock can swing by the option’s expiration, and this probable estimation aids in making informed trading decisions. In this paper, we examine the information content of implied volatility of structured warrants in Singapore Stock Exchange (SGX). Using a daily dataset for 252 trading days for a period between August 1, 2014 and July 31, 2015, we test whether implied volatility is an unbiased estimate of realized volatility, if implied volatility contains information on future realized volatility, scrutinize the efficiency of implied volatility and its predictive power compared to historical volatility. Our findings suggest that for although implied volatility does contain some relevant information about future volatility, it is a biased forecast of realized volatility, the efficiency threshold of implied volatility is nugatory, and its predictive power is not superior to historical volatility.